2023
DOI: 10.1111/jvh.13834
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of delta hepatitis in Türkiye over three decades: A systematic review

Abstract: Hepatitis D virus (HDV) infection leads to severe acute and chronic liver disease in patients infected with hepatitis B virus (HBV). It is common among HBV-infected patients globally. HDV has an estimated prevalence of 4.5% among HBsAg-positive individuals. It is responsible for an estimated 18% of cirrhosis and 20% of HCC associated with hepatitis B. 1 An estimated 257-291 million people are chronically infected with HBV, 2 corresponding to 11-13 million individuals coinfected with HDV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…A recent systematic study was published by Uraz et al [19] ; using a very simple methodology, the authors calculated a mean, adding each prevalence from various studies, of which some studies included very few subjects. With this debatable methodology, Uraz et al [19] reported that after 2010, the anti-HDV prevalence was 5.5% for all patients with HBV infection without cirrhosis (with an HDV prevalence estimate of 5.2% in inactive HBsAg carriers and of 6.9% in patients with CHB). Their estimate falls above the high range of our 95% CI (4.00-6.23) for all HBsAg-positive patients without cirrhosis (outpatient studies).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic study was published by Uraz et al [19] ; using a very simple methodology, the authors calculated a mean, adding each prevalence from various studies, of which some studies included very few subjects. With this debatable methodology, Uraz et al [19] reported that after 2010, the anti-HDV prevalence was 5.5% for all patients with HBV infection without cirrhosis (with an HDV prevalence estimate of 5.2% in inactive HBsAg carriers and of 6.9% in patients with CHB). Their estimate falls above the high range of our 95% CI (4.00-6.23) for all HBsAg-positive patients without cirrhosis (outpatient studies).…”
Section: Discussionmentioning
confidence: 99%
“…Global prevalence of HDV was higher in 1977-1996 than in 1997-2016, however, an opposite trend was observed in some countries, like Japan and Gabon [134]. A study from Turkey demonstrated an overall decrease in HDV prevalence from 8.3% observed in years before 1999 to 5.5% after 2010 [122]. In Italy, the decline in incidence of acute hepatitis D occurred in parallel with the decrease in incidence of acute hepatitis B, suggesting an effect of hepatitis B vaccination on both infections [123].…”
Section: Reduction In Hepatitis D Virus Infectionsmentioning
confidence: 99%